Emozioni estetiche: una critica delle quasi-emozioni di K. Walton (Lebenswelt. Aesthetics and philosophy of experience., 2023)
Kendall Walton’s Mimesis as make believe (1990) is a pivotal text in understanding the receiver’s role during aesthetic experience. Within his theory, aesthetic emotions have a specific importance, and they are considered as quasi-emotions. In this essay, Walton’s account, will be criticised, as it is based on the inappropriate and inconsistent concept of quasi-emotions. Firstly, quasi-emotions entail a mimetic and dualistic perspective on real and fictional words. Moreover, quasi-emotions make Walton’s theory relevant to understand only artistic fruition, and not aesthetic experience.